Evaluations of microvascular density by optical coherence tomography, angiography, and function by multifocal electroretinography of the macular area in eyes with branch retinal artery occlusion - Igawa, Yuro; Amaki, Haruna; Kanno, Junji; Tachibana, Midori; Konno, Satomi; Yoshikawa, Yuji; Matsumoto, Soiti; Shoji, Takuhei; Makita, Jun; Shinoda, Kei (Frontiers in Ophthalmology, 2023)
Introduction It is reported that eyes with a branch retinal artery occlusion (BRAO) had normal full-field electroretinography (ERG) but the response of the multifocal electroretinography (mfERG) was reduced in the area of the arterial occlusion. Optical coherence tomography angiography (OCTA) is a recently appeared modality that can evaluate microvascularizations in different retinal layers and in different regions of the retina. The purpose of this study was to determine the density of the microcirculation and the function of the macular area of eyes with BRAO, and to determine whether they are significantly correlated. Methods The OCTA and mfERG findings of 7 eyes of 6 patients (3 men, 3 women) were studied. The mean age of the patients was 71.7±10.6 years. The OCTA examinations were made with volume scans of 3 × 3 and 6 × 6 mm squares centered on the fovea. The macular vessel densities (mVD) in the superficial retinal layer (SRL) and deep retinal layer (DRL) were measured for the superior and inferior halves of 3 × 3 and 6 × 6 mm diameter concentric circles. The mfERGs were recorded with targets set to stimulate the focal areas of the retina corresponding to the areas examined by OCTA. Results The OCTA examinations showed that the mVD of the 3 mm concentric circle in the SRL was significantly lower on the affected side than on the unaffected side (P = 0.022). No such difference was observed in the DRL. The N1 amplitude of the 20.2° concentric circle and the N1–P1 amplitude of the 10.1° concentric circle of the mfERGs were significantly smaller on the affected side than on the unaffected side (P = 0.047 and 0.031). A significant positive correlation was found between the mVD of the 6 mm concentric circle in the DRL and the P1–N2 amplitude of the 20.2° concentric circle (ρ = −0.929 and p = 0.003). Discussion These findings indicate that OCTA images may be able to show changes in the density of the retinal macular microcirculation, and the mfERGs may be able to show alterations in the function of the macular area of the eyes with BRAO. A layer-by-layer analysis of the local retinal microcirculation and function should help in determining the pathogenesis of BRAO.